Sensory Processing and Community Participation in Autistic Adults - Bagatell, Nancy; Chan, Dara V.; Syu, Ya-Cing; Lamarche, Elena M.; Klinger, Laura G. (Frontiers in Psychology, 2022)
Background: Sensory processing differences have been shown to impact involvement in community activities. However, relatively little is known about how these differences affect community participation in autistic adults. Objective: This objective was to explore how autistic adults’ sensory processing patterns impact to participation in the community, including where people go, what they do, the amount of time in the community, and preferred locations. Methods: We used data gathered from six autistic adults and their caregivers who participated in two studies. From Study 1, we reviewed results of the Adolescent and Adult Sensory Profile and transcripts from interviews with caregivers. From Study 2, we reviewed GPS tracking data and transcripts from structured interviews with autistic adults focused on community participation. Participant narratives were constructed linking sensory processing patterns to community participation. Results: Each participant had a unique sensory processing profile that influenced where people went, the activities in which they engaged, how much time they spent in the community, and their preferred locations. Those whose sensory processing patterns indicated sensory sensitivity and sensory avoiding described the experience of certain environments as overwhelming and fatiguing and thus spent less time in the community and visited fewer places than those with other sensory processing patterns. Conclusions: Results highlight the importance of sensory processing, especially as it impacts participation in the community. Sensory processing patterns should be considered along with other personal and contextual factors when assessing community participation and personal sensory processing patterns should be matched with activities and environmental demands